Study of depressive disorder in cancer patients at the department of oncology, Hue University Hospital in 2016 - Tran, Doan Quoc Long; Tran, Thao Vi; Ton, Nu Nhi Hoang; Ho, Thi Ngoc Dung; Phan, Thi My Hao; Lam, Phan Lien Nhi; Nguyen, Thi Dang Thu; Ho, Xuan Dung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Overview: Depression is an issue that is concerning in cancer patients. It makes the clinical picture of the cancer patients more complex, more difficult to be treated and it increases the risk of death. However, the diagnosis of depressive disorder in patients with cancer and the desires of them during the treatment course still have not been concerned in Vietnam. Objectives: 1. To determine the prevalence of depression in cancer patients at the department of oncology- Hue University Hospital in 2016. 2. To find out the correlated factors of the depressive disorder in cancer patients. 3. To know some desires of patients with cancer. Methods: A descriptive cross-sectional study on 102 cancer patients being treated at the department of Oncology, Hue University Hospital. Using the questionnaires for interviewing and the Beck Depression Inventory (short form) to assess the level of depression. Results: The rate of depression in cancer patients was 70.6%, including 23.5% with mild depression, 36.3% had moderate depression and severe depression accounted for 10.8%. The rate of moderate depression in female patients (46.2%) was higher than that of males (26%), p=0.035. All cancer patients with stage I had the symptoms of mild depression but in patients with stage IV was only accounted for 19.3%, p<0.05. There was an association between severe depression and the difficulty of treatment fees payment of the cancer patients, p<0.05. There were 60.8% of patients who wanted to be explained their illness. During the course of treatment, 57.8% of patients wished to have psychological support. In addition, patients desired to have some cultural activities at the hospital (32.4%), frequently having someone to talk with (31.4%), receiving good care and guidance from the medical staff (28.4%). Conclusion: The rate of depression in cancer patients was 70.6%. There was an association between moderate depression and gender, between mild depression and cancer stage, between severe depression and difficulty in paying hospital fee. In addition, patients have a lot of desires in order to improve the quality of treatment at the hospital.